Breaking the Chain of Digital Dependency: A call to Arms for Responsible Parenting - Fatima, Mishal (Journal of Pakistan Psychiatric Society, 2025)
In an era overwhelmingly dominated by digital screens, the role of parents has become pivotal, yet paradoxically, many inadvertently contribute to their children's dependence on digital devices. Left unaddressed, this reliance can significantly impact children's physical, mental, and emotional well-being, necessitating a reevaluation of parental approaches towards technology's influence on their children's lives. Over the past two decades, technological advancements have permeated every aspect of society, with digital devices ranging from smartphones to social media platforms becoming ubiquitous. While technology undeniably offers numerous benefits, excessive usage can lead to detrimental effects, particularly among children.